2021
DOI: 10.1140/epjd/s10053-021-00138-z
|View full text |Cite
|
Sign up to set email alerts
|

Effective ionization coefficients for low current dc discharges in alcohol vapours at low pressure

Abstract: This paper presents results for effective ionisation coefficients ($$\alpha _{\mathrm {eff}}/N$$ α eff / N , N—gas density) obtained from the breakdown voltage and emission profile measurements in low-pressure dc discharges in vapours of alcohols: methanol, ethanol, isopropanol, and n-butanol. Our results for $$\alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
3
0
1
Order By: Relevance
“…For the reduced ionization coefficient, we have experimental values reported in the literature for all the studied alcohols with E/N values from 130 Td and with a maximum of 8800 Td [37,[40][41][42]. There is a good agreement in the profile of the obtained data presented in Figure 6 for methanol and ethanol which have a better-defined cross-section set in the range where the calculations were performed.…”
Section: Reduced Ionization Coefficientsupporting
confidence: 56%
See 1 more Smart Citation
“…For the reduced ionization coefficient, we have experimental values reported in the literature for all the studied alcohols with E/N values from 130 Td and with a maximum of 8800 Td [37,[40][41][42]. There is a good agreement in the profile of the obtained data presented in Figure 6 for methanol and ethanol which have a better-defined cross-section set in the range where the calculations were performed.…”
Section: Reduced Ionization Coefficientsupporting
confidence: 56%
“…Reduced ionization coefficient for (a) Methanol, (b) Ethanol, (c) Propanol, (d) Butanol as a function of E/N. (solid lines from BOLSIG+ (B+), and solid line-point from METHES (MT), subscript (T) theoretical and (X) experimental data set cross-section, solid circles experimental data from Hasegawa and Date[37], Marjanović et al[40], Schlumbohm and Angew[41] and Engel[42]…”
mentioning
confidence: 99%
“…where D L is the longitudinal diffusion coefficient, ν ef f is the effective ionization frequency (equal to ionization frequency minus attachment frequency), and W is the bulk drift velocity, which gives the velocity of the center-of-mass of the electron cloud, parameters already obtained and demonstrated [42]. There are experimental values of α reported in the literature for all the studied alcohols with E/N values from 130 Td to 8800 Td [39,[43][44][45]. Figure 6 collects them and the obtained data.…”
Section: Reduced Ionization Coefficientmentioning
confidence: 97%
“…92) Further investigation showed that the effective ionization coefficients for the alcohol vapors were measured by breakdown voltage and emission profile measurements in low-pressure DC discharges. 93) Electron collision cross-sections of dimethyl ether (DME, C 2 H 6 O) were measured under a constant electric field and crossed electric and magnetic fields through the standard swarm analysis. 94) A multiple term solution of the BE for electron noble gases, including He, Ne, Ar, Kr, and Xe, were discussed by considering the third-order transport coefficient tensor 95) and the effect of longitudinal field components on the spatial profile of electron swarms.…”
Section: 5mentioning
confidence: 99%